Perbedaan Pemberian Metode Bom Massage Terhadap Kelancaran ASI Pada Ibu Post Partum - Umarianti, Tresia; Putriningrum, Rahajeng; Prasetyoningsih, Aris; Widyastutik, Desy; Wulandari, Retno; Yessy Maretta, Megayana; Prasetyo, Budi (Universitas Muhammadiyah Klaten, 2023)
The BOM massage method is stimulation to help produce and expel breast milk as well as a combination of ways to care for the breasts so that milk can produce and provide relaxation for postpartum mothers. Mothers after giving birth can experience psychological fatigue associated with anxiety or depression which can hinder the flow of breast milk. Breastfeeding mothers who are always in a state of stress, sadness, anxiety, and experience various forms of tension will result in inhibition of the prolactin and oxytocin hormone systems, both of which are very influential and play an important role in the process of milk secretion. This study aims to analyze the differences in giving the BOM Massage method to the smoothness of breastfeeding in Post Partum Mothers. Analytical experimental research with RCT (Randomized Controlled Trial) design. The research was conducted at PMB Fitri Handayani. The subject of the study was the Postpartum Mother with a total of 20 respondents divided into 2 groups, 10 people per group were each treated with the BOM Massage method by giving 1 time a day for 2 days and 2 times a day for 2 days. The sampling method was purposive sampling, using the Paired T-test. Results Test the differences in the BOM Massage method once a day for 2 days lower (mean= 7.70; SD= 1.77) compared to 1 day twice for 2 days (mean= 10.3; SD= 1.25) Results statistical test Paired T-test has the effect of the BOM Massage method on the smoothness of ASI with a p value <0.001. In conclusion, giving the BOM Massage method 2 times a day for 2 days is more effective for smooth breastfeeding in Cemani Sukoharjo